Dynamic alterations in decoy VEGF receptor-1 stability regulate angiogenesis - Joshua M. Boucher (Nature Portfolio, 2017)
Membrane-bound mVEGFR1 is a decoy VEGF-A receptor that regulates VEGF-A signalling amplitude. Boucheret al. show that Rab27a-regulated palmitoylation of mVEGFR1 redirects the receptor from a stable, constitutively recycling mode to a degradative route that removes ligands from the system.